The End of Life As “Non” Death - Tarca, Luigi Vero (ETHICS IN PROGRESS, 2019)
Taking the cue from some verses of Rilke’s Duineser Elegien, where the poet talks about the distinction between life and death, a distinction which mortals perform too rigidly, in this paper I discuss the contrast just between life and death, in order to understand the conditions under which the first truly distinguishes itself from the latter. This happens to the extent that life is also distinguished from the denial of death because otherwise, being the negation a form of necation (nex = killing, murder), the presumed denial of death would reverse in a triumph of death. In the present age this circumstance is particularly evident and significant, since humanity aims at a technological realization of im‑mortality, understood as the denial of death. To the extent that this remains a negative operation, it takes the form of the scrapping of mortals. True liberation/salvation from death presupposes that the negation itself is called into question. Only on this condition, in fact, is possible a life free from any form of necation. This freedom presupposes, inter alia, a “non” education, intended as an education to be able to freely play with the negative of death and denial.